Why the Manufacturing Sector Still Matters for Growth and Development in Indonesia - Rahardja, Sjamsu; Winkler, Deborah; Varela, G.; Ing, Lili Yan (World Bank, Jakarta, 2017)
Is Indonesia's manufacturing sector still relevant for growth and development? As a result of the last boom in global commodity prices between 2003 and 2008, resources in Indonesia shifted towards commodities and resource-based manufacturing as these sectors seemed to promise higher returns on investment. In recent quarters, however, the manufacturing sector has exhibited stronger output growth rates and attracted more investment. This note argues that building on the current momentum of manufacturing growth is critical for Indonesia's development (i) to support the creation of higher-productivity jobs, (ii) to sustain higher economic growth and progress in structural change, and (iii) to achieve long-term prosperity. Finally, this note also shows how the Master Plan for the acceleration and expansion of Indonesia's economic development (MP3EI) acknowledges the importance of the manufacturing sector for economic growth.